2019
DOI: 10.3390/v11040373
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Humoral Immune Response during Ebola Virus Infection in Survivor and Fatal Cases Occurred in Sierra Leone during the 2014–2016 Outbreak in West Africa

Abstract: Ebola virus (EBOV) infection is characterized by an excessive inflammatory response, a loss of lymphocytes and a general paralysis of the immune system, however pathophysiological mechanisms are not fully understood. In a cohort of 23 fatal and 21 survivors of ebola virus disease (EVD) cases admitted to the Emergency Ebola-Treatment-Center in Goderich (Freetown, Sierra Leone) during the 2014 to 2016 EBOV epidemic in Western Africa, we analyzed the pathway-focused gene expression profile of secreted proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…SARS-CoV-2 RNA performed by real-time RT-PCR on respiratory secretions, or on clinical symptoms plus the presence of SARS-CoV-2specific antibodies by the reference method employed in the laboratory. This method is an indirect immunofluorescence assay (IFA), established using home-made slides prepared with Vero E6 cells infected with SARS-CoV-2 isolate in the INMI BSL3 facility, as described elsewhere [7].…”
Section: Objectivesmentioning
confidence: 99%
“…SARS-CoV-2 RNA performed by real-time RT-PCR on respiratory secretions, or on clinical symptoms plus the presence of SARS-CoV-2specific antibodies by the reference method employed in the laboratory. This method is an indirect immunofluorescence assay (IFA), established using home-made slides prepared with Vero E6 cells infected with SARS-CoV-2 isolate in the INMI BSL3 facility, as described elsewhere [7].…”
Section: Objectivesmentioning
confidence: 99%
“…EBOV_S have robust EBOV-specific memory T cell responses. Characterization of EBOV-specific T cell responses in Ebola infection are still limited and most of the studies evaluated these responses either during the acute or the recovery phase of EBOV infection comparing EBOV_S and fatal cases [11][12][13][14][15][16][17] . We assessed whether EBOV-specific T cells would become detectable after antigen-specific in vitro T cell expansion.…”
Section: Chronic Activation and Microbial Translocation In Ebov_smentioning
confidence: 99%
“…The immune responses of EVD patients have been reported during acute-phase infection or soon after the resolution of infection [11][12][13][14][15][16][17] . These studies identified immune signatures associated with death from EVD rather than survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These research efforts have significantly improved our understanding of EVD pathophysiology and immunity. Regarding the latter, findings from several laboratories indicate that acute EVD is characterized by exacerbated and sustained adaptive immune responses [2][3][4] and that both arms of the adaptive immunity are critical for recovery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%